Studi Kualitatif Manajemen Strategi IGD RS A dalam Menghadapi COVID-19 sebagai Input untuk Tata Laksana Ancaman Wabah Penyakit Infeksi - Willy Johan; Ida Ayu Nitri Saraswati; Karunia Meilani Nurfatika; Dian Angger Suaner; Poppy Putri Pratiwi; Muhammad Arief Kusuma; Alphonsus Arya Arbikara; Mira Veranita (Cermin Dunia Kedokteran, 2024)
Background: Reflecting on the COVID pandemic, many emergency departments (ED) experienced difficulties in responding to health crises caused by emerging infectious diseases. This qualitative research explores the strategic management of one of the hospital EDs assigned as a COVID referral hospital. Methods: In-depth interviews with 10 key informants, observation, and document analysis. Peer discussions with experts were also carried out to ensure the validity of the existing data. Results: The research results show that RS A prepared surge capacity (space, staff, supply, and system) before the crisis, and the disaster management system has been prepared and continuously updated. Conclusion: In addition to being designed to optimize medical services for emergency patients, emergency departments must also be prepared to deal with disasters. The spare capacity that has been prepared by the Hospital A Emergency Unit in the face of disasters can be fully utilized in the COVID-19 pandemic.